TEH HIJAU DAN TEH HITAM MAMPU MENURUNKAN KADAR KOLESTEROL LDL HEWAN COBA MODEL HIPERLIPIDEMIA - Dhany Pratama Tindage; Rita Dewi; Jojor L. Manalu (Atma Jaya Catholic University of Indonesia, 2021)
Introduction: Hyperlipidemia is a global health problem with the number of sufferers increasing every year. Globally, one-third of heart disease is caused by high cholesterol levels including LDL cholesterol. Overall, hypercholesterolemia is estimated to cause 2.6 million deaths. Green tea and black tea can be alternatives to traditional medicine. Some researches state that tea consumption is good for health. Green tea and black tea can be used as an alternative treatment in reducing LDL cholesterol levels in patients with hyperlipidemia. Method: This study is an in vivo experimental research. This experiment using 16 Rattus norvegicus rats Sprague Dawley strain induced into hyperlipidemia with lard and quail egg yolks before and divided into 2 groups; the green tea group and the black tea group. Interventions carried out for 17 days and checking the blood LDL cholesterol at the beginning and at the end of the intervention using Friedewald’s formula with HDL, total cholesterol and triglycerides numbers from cholesterol test strip and tools from Lipid Pro. Data were collected and analyzed using the Shapiro-Wilk test, Wilcoxon Matched-Pair Signed-Ranks Test, Mann-Whitney U Test. Result: The results showed that the data were normally distributed (Shapiro-Wilk test p>0.05). Intervention with green tea and black tea for 17 days led to a significant drop in LDL cholesterol levels (Wilcoxon Matched-Pair Signed-Ranks Test p<0.05), but there is no significant difference between the effectiveness of the treatment group (Mann-Whitney U Test p>0.05). Conclusion: There were no differences in effectiveness of green tea compared with black tea in lowering LDL cholesterol levels on hyperlipidemic Rattus norvegicus, but both green tea and black tea can lower rats’ total cholesterol levels significantly.